1999
DOI: 10.1177/104973159900900205
|View full text |Cite
|
Sign up to set email alerts
|

Social Work Services on an Organ Transplantation Program: A Preliminary Cost-Benefit Analysis

Abstract: Objective: A prospective clinical trial was conducted to measure the effectiveness and cost-benefit of social work clinical practice on a multi-organ transplant program. Method: Recipient financial, clinical, and quality-of-life data were collected for patients who received organ transplants in 1995 ( N= 105) at Integris Oklahoma Transplantation Institute. Results: The income produced for the organization exceeded the cost of providing social work services but demonstrated only a limited ability to reduce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…It has been our experience that counseling significantly improves outcomes and quality of life for patients at psychosocial risk. 12 Surprisingly, the choice of psychological technique seems to be the least important factor. The key elements are the patient's recognition that a problem exists and her agreement to participate in a treatment regimen-a commitment that is absent in this case.…”
Section: Resultsmentioning
confidence: 99%
“…It has been our experience that counseling significantly improves outcomes and quality of life for patients at psychosocial risk. 12 Surprisingly, the choice of psychological technique seems to be the least important factor. The key elements are the patient's recognition that a problem exists and her agreement to participate in a treatment regimen-a commitment that is absent in this case.…”
Section: Resultsmentioning
confidence: 99%
“…Published studies have shown that transplant recipients benefit from structured psychological treatment in the following ways: reduced morbidity and mortality for recipients at psychosocial risk, 20 reduced family dysfunction and better overall adjustment, 21 reduction in stress-related problems, 22 reduced risk of substance abuse relapse, 2 and maximum use and benefit of staff interventions when those at greatest need for psychosocial services are identified. 23 Other studies have shown that when there is an absence of adequate psychosocial assessment and/or treatment, the results are less than ideal. 1,8 These findings suggest that psychosocial risk itself does not portend a negative outcome; outcome depends on whether the transplant team and the individual patient have made a serious committment to psychosocial assessment and treatment.…”
Section: A Pattern Of Unstable and Intense Interpersonal Relation-mentioning
confidence: 99%
“…19,20 Assessment of such a network is primarily in the professional domain of the transplant social worker and other transplant team members who focus on psychological and social components of transplantation. 21,22 Individual characteristics of transplant recipients are of immediate concern and importance to transplant team professionals and researchers and in total recovery treatment models. In this study, we selected sex, race, and social class exclusively because, first, these characteristics repeatedly appeared as practical linkages for elucidating social support networks during clinical assessments by transplant team members.17 Second, race and social class were also indicated in a recent review of literature as significant variables factoring into social support.…”
mentioning
confidence: 99%